Synergetic Innovation in Social Governance in a Complex Network Structural Paradigm*. (2nd April 2016) - Ruguo, Fan
Abstract : Society is in essence a complex network system that is open, evolving and adaptable and possesses a coupling function. Social governance is a large-scale and complex systems engineering project. Due to the complexity and uncertainty of the environment and social affairs, the traditional government-led linear management model cannot provide effective interpretations and responses to complex social issues, and it is thus necessary to introduce the complexity scientific paradigm. Complexity science, especially complex system theory, has an intrinsic correspondence with social governance, and can reveal the inherent occurrence mechanism and rules brought about by the complexity of social governance. It indicates that the more complex a system is, the greater will be its requirements for systemic coordination and the more apparent its synergetic effects. A complex social network system is small-world and scale-free, with a community structure, preferential attachment and a topological structure characterized by the duality of virtuality and actuality. All of these have a direct and profound effect on social governance. To strengthen and innovate social governance, it is necessary to analyze the social system's complex network structure and characteristics, establish synergetic and innovative mechanisms and institutional arrangements for social governance, and carry out synergetic social governance.